Increasing kinesthetic intelligence through outbound kapla toys - Noor, Fu'ad Arif; Indriani, Indah; Khairiah, Dina (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: Outbound Kapla Toys is an outdoor play activity that can develop children's gross motor skills by crawling, jumping, hopping and throwing according to the correct color. The kinesthetic intelligence of children at RA Nurul Huda Sidokumpul Guntur Demak has not developed optimally, this is evident from the fact that most children have difficulty in doing these basic movements. This activity stimulates their imagination and creativity, because there are no limits to what they can create.Aim: To determine the implementation of kinesthetic learning and its improvement at RA Nurul Huda Sidokumpul Guntur Demak through Outbound Kapla Toys. The novelty of this study compared to previous studies lies in a more holistic and multidimensional approach to developing children's skills, compared to previous studies that focused more on one aspect such as motor skills or creativity.Method: The subjects of this classroom action research (CAR) were children aged 5-6 years at RA Nurul Huda Sidokumpul Guntur Demak. The data collection instruments used observation, interviews and documentation.Results: Outbound Kapla can be used to build various shapes and designs, which support the development of children's fine motor skills and creativity. In the implementation of kinesthetic learning, it increases and develops very well.Conclusion: Kinesthetic Intelligence through Kapla Outbound Toys increases and is able to display basic movements that are easy for children to do so that it is effective to use.